Dopamine effects on memory load and distraction during visuospatial working memory in cognitively normal Parkinson's disease. Issue 6 (2nd November 2021) - Bayram, Ece; Litvan, Irene; Wright, Brenton A.; Grembowski, Cailey; Shen, Qian; Harrington, Deborah L.
ABSTRACT: Visuospatial working memory (WM) impairments in Parkinson's disease (PD) are more prominent and evolve earlier than verbal WM deficits, suggesting some differences in underlying pathology. WM is regulated by dopaminergic neurotransmission in the prefrontal cortex, but the effect of dopamine on specific processes supporting visuospatial WM are not well understood. Dopamine therapeutic effects on different WM processes may also differ given the heterogeneity of cognitive changes in PD. The present study examined the effect of dopamine therapy on memory load and distraction during visuospatial WM. Exploratory analyses evaluated whether individual differences in medication effects were associated with a gene, catechol-O-methyltransferase (COMT), which regulates prefrontal cortex dopamine levels. Cognitively normal PD participants (n = 28) and controls (n = 25) performed a visuospatial WM task, which manipulated memory load and the presence/absence of distractors. PD participants performed the task on and off medication. PD COMT groups were comprised of Met homozygote (lower COMT activity) and heterozygote and Val homozygote carriers (higher COMT activity, Het/Val). The results showed that handling higher memory loads and suppressing distraction were impaired in PD off, but not on medication. Medication improved distraction resistance in Met, but not Het/Val group. COMT did not modulate medication effects on memory load. These findings demonstrate that dopaminergic therapy restores visuospatial WM processes in patients without cognitive impairment and suggest that COMT variants may partly explain the mixed effects of medication on specific processes governed by distinct brain systems. Future investigations into gene-modulated effects of medication could lead to individualized strategies for treating cognitive decline.